Spatio-temporal decoupling of stomatal and mesophyll conductance induced by vein cutting in leaves of Helianthus annuus - Hanson, David T.; Green, Laura E.; Pockman, William (Frontiers in Plant Science, 2013)
Reduction of hydraulic conductance to the canopy has been shown to result in stomatal responses to limit transpiration. To test for similar responses to perturbations of the hydraulic network in leaves, we simultaneously measured leaf gas exchange with spatially explicit chlorophyll-a fluorescence and leaf temperature to examine the effects of cutting a primary leaf vein in Helianthus annuus. We repeated the leaf treatment at each of three different vapor pressure deficits and monitored the short-term dynamics of gas exchange following the treatment. Immediately after treatment, photosynthesis and stomatal conductance showed a transient “wrong-way” response in which photosynthesis declined despite increased stomatal conductance. Comparisons of fluorescence and temperature across the leaf showed that both photosynthesis and stomatal conductance were transiently patchy across the measured leaf area, but that the patchiness of the two processes did not correspond in space or time. This suggests that photosynthesis and stomatal conductance respond to vein cutting-induced cavitation via different mechanisms. Because the stomatal response varied by VPD condition but photosynthesis did not, it is likely that stomatal conductance, but not photosynthesis, responded to a hydraulic signal. In contrast, we hypothesize that photosynthesis declined due to a wound-induced electrical signal that has recently been shown to transiently decrease mesophyll conductance to CO2. The interaction of epidermal hydraulics and the electrical signal across the leaf likely created a patchy pattern of chlorophyll fluorescence and leaf temperature that cannot be explained through the action of a single signal.